The effect of soil moisture content and solarization of the soil with solar energy on fungi present in greenhouses (Comprehensive Journal of Science, 2025)
This experiment was conducted on a private farm in Janzour city, to determine the effect of five irrigation levels before sterilization (1, 4, 7, 10, 13 days) on the success and efficiency of the solar sterilization process in eliminating fungi present inside greenhouses. The results obtained confirmed that solar sterilization of soil is an effective method in eliminating dormant fungal groups in the soil. The results also showed that the soil moistening period before (7, 10 days) solar sterilization had the highest effect than the different irrigation levels for either transparent or black plastic cover, especially at depths close to the soil surface.
Keywords: Effect, content, moisture, solarization, soil, fungi